The secret school - Avi, 1937- (San Diego, CA : Harcourt, 2001)
In 1925, fourteen-year-old Ida Bidson secretly takes over as the teacher when the one-room schoolhouse in her remote Colorado area closes unexpectedly.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
4.2.
4.2
3-6
Keywords: Historical fiction; Rural schools -- Fiction; Schools -- Fiction; Sex role -- Fiction; Teachers -- Fiction; Historical fiction; Rural schools -- Fiction; School stories; Sex role -- Fiction; Teachers -- Fiction; Colorado -- Fiction; Colorado -- Fiction